PENDAMPINGAN KELUARGA BERESIKO STUNTING SEBAGAI UPAYA PERCEPATAN PENURUNAN STUNTING DI KOTA PROBOLINGGO - supraptiningsih, linda kurnia; Kumala Devi, Nourma Ulva; Hermanto, Hermanto (Abdi Panca Marga, 2024)
Community service activities are carried out with the aim of providing experience for Panca Marga University students and lecturers in implementing the Merdeka Belajar Kampus Merdeka (MBKM) activities which are realized in the form of Community Service in an effort to reduce the stunting rate in Probolinggo City. Activities in the form of socialization and family assistance with prospective Calon Pengantin (CATIN) who are at risk of stunting in the Probolinggo City area. Assistance to CATIN takes the form of outreach about the impact of early marriage which includes the risk of giving birth to stunted children. KMitra's assistance in this activity is the Community Health Center with the target being pregnant mothers and mothers of toddlers who come to the Posyandu in the Kanigaran Community Health Center Working Area, Kanigaran sub-district which covers the Kanigaran sub-district and the Sukabumi Community Health Center, Sukabumi sub-district which covers the Mayangan sub-district and Mayangan sub-district in Probolinggo City. The choice of location for this activity was based on the population in the two sub-districts, which is relatively larger than other sub-districts in the city of Probolinggo considering that all sub-districts in the city of Probolinggo are registered as stunting loci. Nutrition and health problems, especially in toddlers, can be prevented through educational activities provided through Posyandu activities. The solution carried out in community service activities is in the form of providing assistance and outreach to residents at the specified location. References Kementerian Kesehatan Republik Indonesia. 2018. Hasil Riset Kesehatan Dasar Republik Indonesia Tahun 2018. Jakarta Kementerian Kesehatan Republik Indonesia. 2018. Situasi Balita Pendek di Indonesia. Uliyanti; Tamtomo, D. G. S. A. (2017). Faktor Yang Berhubungan Dengan Kejadian Stunting Pada Balita Usia 24-36 Bulan. Jurnal Ilmu Kesehatan, 11(2), 148. https://doi.org/10.32831/jik.v11i2.451 World Health Organization. (2018). World Health Organization. Reducing stunting in children: equity considerations for achieving the Global Nutrition Targets 2025. World Health Organization; 2018.